Effects of curcumin on performance, antioxidation, intestinal barrier and mitochondrial function in ducks fed corn contaminated with ochratoxin A. (12th April 2018) - Ruan, D.; Wang, W. C.; Lin, C. X.; Fouad, A. M.; Chen, W.; Xia, W. G.; Wang, S.; Luo, X.; Zhang, W. H.; Yan, S. J.; Zheng, C. T.; Yang, L.
Abstract : Curcumin has been attributed with antioxidant, anti-inflammatory, antibacterial activities, and has shown highly protective effects against enteropathogenic bacteria and mycotoxins. Ochratoxin A (OTA) is one of the major intestinal pathogenic mycotoxins. The possible effect of curcumin on the alleviation of enterotoxicity induced by OTA is unknown. The effects of dietary curcumin supplementation on OTA-induced oxidative stress, intestinal barrier and mitochondrial dysfunctions were examined in young ducks. A total of 540 mixed-sex 1-day-old White Pekin ducklings with initial BW (43.4±0.1 g) were randomly assigned into controls (fed only the basal diet), a group fed an OTA-contaminated diet (2 mg/kg feed), and a group fed the same OTA-contaminated feed plus 400 mg/kg of curcumin. Each treatment consisted of six replicates, each containing 30 ducklings and treatment lasted for 21 days. There was a significant decrease in average daily gain (ADG) and increased feed : gain caused by OTA ( P <0.05); curcumin co-treatment prevented the decrease in BW and ADG compared with the OTA group ( P <0.05). Histopathological and ultrastructural examination showed clear signs of enterotoxicity caused by OTA, but these changes were largely prevented by curcumin supplementation. Curcumin decreased the concentrations of interleukin-1 β, tumor necrosis factor- α and malondialdehyde, and increased the activity of glutathione peroxidase induced by OTA in the jejunal mucosa of ducks ( P <0.05). Additionally, curcumin increased jejunal mucosa occludin and tight junction protein 1 mRNA and protein levels, and decreased those of ρ -associated protein kinase 1 ( P <0.05). Notably, curcumin inhibited the increased expression of apoptosis-related genes, and downregulated mitochondrial transcription factors A, B1 and B2 caused by OTA without any effects on RNA polymerase mitochondrial ( P <0.05). These results indicated that curcumin could protect ducks from OTA-induced impairment of intestinal barrier function and mitochondrial integrity.